2022
DOI: 10.3390/su14159484
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Differences between the Environmental Impacts of 44 French Artisanal Cheeses

Abstract: Cheese production causes significant environmental impacts, which have to be reduced. In France, a lot of different cheeses are available, made from different milks but also from different cheese technologies. The goal of this study was to understand the origin of the environmental impact variation between cheeses made from different technologies and milks and produced using different ripening practices. To do so, the environmental impacts of 44 different types of French artisanal cheese, all produced under pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is important to note that the water used during pasteurization for steam generation can be reused in some cases for subsequent pasteurization, while the water used for CIP is typically discarded after use. In an LCA of 44 different artisanal French cheeses for their environmental impact, it was revealed that CIP was responsible for consumption of 10%–29.5% of total water utilized during cheese production (Cortesi et al., 2022). Hence, we can consider CIP to be a major consumer of water during processing.…”
Section: Understanding the Impact Of Energy And Water Usage For Cip I...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the water used during pasteurization for steam generation can be reused in some cases for subsequent pasteurization, while the water used for CIP is typically discarded after use. In an LCA of 44 different artisanal French cheeses for their environmental impact, it was revealed that CIP was responsible for consumption of 10%–29.5% of total water utilized during cheese production (Cortesi et al., 2022). Hence, we can consider CIP to be a major consumer of water during processing.…”
Section: Understanding the Impact Of Energy And Water Usage For Cip I...mentioning
confidence: 99%
“…The cheese industry, which falls under the broader umbrella of dairy processing, utilizes roughly a quarter of the world's raw milk production and is known to be an energy‐intensive process (Xu et al., 2009) and particularly, in the European Union over 39% of the total milk produced is utilized for cheese making (Cortesi et al., 2022). The prevalent impacts of energy and water usage, as well as the use of chemicals in CIP processes, on the broader dairy industry also have implications for the cheese industry.…”
Section: Environmental Considerations For Cipmentioning
confidence: 99%